Review of Obstruction of Justice Perpetrators in Premeditated Murder Cases - Hasiholan Tua; Emilia Susanti (CV. Publikasi Indonesia, 2024)
Criminal responsibility is a reprehensible act by society that must be accounted to its maker for the actions committed. The problem in this study is how criminal accountability for perpetrators of obstruction of justice in premeditated murder cases and whether the sentences given to perpetrators have fulfilled the sense of substantive justice for the community (Review of Verdict Number: 806 / Pid, Sus / 2022 / PN Jkt Sel). The research method uses a normative juridical approach, the data used are secondary. The study conducted is a literature study. The resource person in this study is a Criminal Lecturer at the Faculty of Law, University of Lampung. This study aims to see in depth how criminal responsibility for perpetrators of criminal acts of persecution and whether the verdict given has fulfilled the sense of justice for the community, therefore the approach taken in this study is normative. Based on the results of research and discussion, it can be concluded that after listening to witness statements and legal facts at the trial and based on the judge's consideration, the defendant was sentenced to imprisonment for 10 (ten) months and a fine of Rp. 10,000,000 (ten million rupiah), because the elements have been legally and convincingly proven. In addition, Judgment No.: 806/Pid. Sus/2022/PN Jkt Sel has fulfilled the substantive sense of justice as the panel of judges has carefully considered and decided to issue this ruling.